Inheritance of Work Culture as Informal Education: A Qualitative Study of the Woodworking Community of West Java, Indonesia - Mustakim, Mustakim; Supriyono, Supriyono; Dayati , Umi; Ishaq , M; Mohamed, Suziyani; Susilo, Heryanto (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
This study aims to examine the elements of work culture inheritance, inheritance processes, and informal learning strategies in the carpentry community in Tasikmalaya, West Java, Indonesia. The research approach used is a case study with data collection techniques through observation and interviews. The results of the study show that elements of work culture are inherited through informal learning based on direct practice, the use of Sundanese as the main medium, the maintenance of kinship values, and the combination of manual and machine technology in production activities. The majority of the community still depends on woodcraft for their livelihood, upholds Islamic cultural identity, and preserves the heritage of kelom geulis woodcraft. The process of cultural inheritance takes place through transformative, internalization, and transinternalization phases, and is strengthened by socialization mechanisms (through imitation) and enculturation (through life experiences, social interactions, and market dynamics). Informal learning strategies are carried out independently, utilizing learning resources from experienced people close to the individual, and are oriented towards market needs. The implications of this research emphasize the role of traditional communities as effective informal educational institutions in maintaining the sustainability of work skills and cultural values. Scientifically, these findings enrich the literature on non-formal education and cultural sociology, while providing a conceptual contribution to the understanding of the inheritance of traditional work skills in the context of modernization and socio-economic change in Indonesia. Keywords: inheritance of work culture, informal education, woodworking, enculturation and internalization, traditional community